Graeme Murphy addresses the dancers on the first day of rehearsal for Vast, 1988 - Gaica, Branco, 1950- (1988)
The dancers are from 4 companies: Australian Dance Theatre, West Australian Ballet, the Queensland Ballet and Sydney Dance Company. The production premiered at the Palais Theatre, Melbourne, on 4 March 1988 before touring nationally to Adelaide, Perth, Brisbane and Sydney.
Title devised by cataloguer based on labels on verso.
Condition: Good.
Choreographed by Graeme Murphy.
Part of the collection: Rehearsals of Vast, created by Graeme Murphy for the National Bicentennial Dance Event, 1988.
Inscriptions: "7/3" in ink on reverse; label and photographer's stamp on reverse.
Also available online
Keywords: Murphy, Graeme, -- 1950- -- Photographs; National Bicentennial Dance Event -- Photographs; Vast (Choreographic work : Murphy) -- Photographs; Dance -- Australia -- Photographs; Dancers -- Australia -- Photographs; Dancers